PRINSIP PENDIDIKAN PERSPEKTIF AL-QUR’AN DAN HADITS - Khonsa' Az Zahroh; Sriyono Fauzi (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Education is a fundamental element of life that plays a crucial role in shaping the personality, ethical values, and intellectual capacity of both individuals and society. Meanwhile, Islamic education does not focus solely on worldly matters but also aims to cultivate individuals who are God-fearing and possess noble character. In an increasingly diverse and complex era, the world of education faces various challenges, such as a moral crisis, a decline in values, and inequality in access to education. Therefore, the primary sources of Islamic teachings—the Qur’an and the Hadits—serve as the foundation and solution for Islamic education, as they contain profound and timeless educational principles. Thus, the objective of this study is to further explore the educational principles found in the Qur’an and Hadits and their relationship to education. The method used in this study is library research, which involves collecting books or works relevant to the topic under investigation. The results of this study indicate that the educational principles from the perspective of the Qur’an and Hadits consist of 1.) Sincerity, 2.) Justice and honesty in education, 3.) Lifelong education, 4.) Development of Fitrah, and 5.) The process of educational internalization.